Sleep Disorder Diagnosis During Pregnancy and Risk of Preterm Birth. Issue 3 (September 2017) - Felder, Jennifer N.; Baer, Rebecca J.; Rand, Larry; Jelliffe-Pawlowski, Laura L.; Prather, Aric A.
Abstract : OBJECTIVE: To test the hypothesis that sleep disorder diagnosis would be associated with increased risk of preterm birth and to examine risk by gestational age, preterm birth type, and specific sleep disorder (insomnia, sleep apnea, movement disorder, and other). METHODS: In this observational study, participants were from a cohort of nearly 3 million women in California between 2007 and 2012. Inclusion criteria were women with singleton neonates liveborn between 20 and 44 weeks of gestation without chromosomal abnormalities or major structural birth defects linked to a hospital discharge database maintained by the California Office of Statewide Health Planning and Development and without mental illness during pregnancy. Sleep disorder was defined based on International Classification of Diseases, 9th Revision, Clinical Modification diagnostic code (n=2, 265). Propensity score matching was used to select a referent population at a one-to-one ratio. Odds of preterm birth were examined by gestational age (less than 34 weeks, 34–36 weeks, and less than 37 weeks of gestation) and type (spontaneous, indicated). RESULTS: Prevalence of preterm birth (before 37 weeks of gestation) was 10.9% in the referent group compared with 14.6% among women with a recorded sleep disorder diagnosis. Compared with the referent group, odds (95% CI, P value, percentage) of preterm birth were 1.3 (1.0–1.7, P =.023, 14.1%) for insomnia and 1.5 (1.2–1.8, P <.001, 15.5%) for sleep apnea. Risk varied by gestational age and preterm birth type. Odds of preterm birth were not significantly increased for sleep-related movement disorders or other sleep disorders. CONCLUSION: Insomnia and sleep apnea were associated with significantly increased risk of preterm birth. Considering the high prevalence of sleep disorders during pregnancy and availability of evidence-based nonpharmacologic interventions, current findings suggest that screening for severe presentations would be prudent. Abstract : Insomnia disorder and sleep apnea are associated with increased risk of preterm birth.